Musculoskeletal disorders among older hospital cleaners: a systematic review of prevalence and risk factors - Zhou, Wei; Gu, Kaizhi; Chen, Yiyu (Frontiers in Public Health, 2025)
IntroductionHospital cleaning involves unique risk factors including chemical exposures, infection control procedures, and physically demanding tasks that may have greater impact on older workers compared to their younger counterparts. While existing systematic reviews have examined musculoskeletal disorders among cleaning workers, none have specifically focused on older hospital cleaners. With global workforce aging and increasing employment of older adults in healthcare settings, understanding musculoskeletal disorder prevalence and specific risk factors in this population is essential for developing targeted prevention strategies. The primary objective of this systematic review is to determine the prevalence of musculoskeletal disorders among older hospital cleaners and identify associated risk factors.MethodsWe searched PubMed, MEDLINE, Web of Science, and Google Scholar from inception to July 11, 2025. Two reviewers independently screened titles, abstracts, and full texts. Data extraction included study characteristics, participant demographics, prevalence data, and risk factors. Quality assessment was conducted using the Joanna Briggs Institute checklist.ResultsEleven studies were included. Among older hospital cleaners (aged 50+ years), musculoskeletal disorder prevalence ranged from 49.1% to 68.96% across age-stratified studies. Several factors appeared to be associated with MSD risk in this population, including work demands, individual factors (age, gender, inadequate rest time, stress, and posture), technology-related factors, and organizational factors.DiscussionThis systematic review identified multiple risk factors for musculoskeletal disorders among older hospital cleaners. The findings provide evidence to inform occupational health policies and targeted prevention strategies for this vulnerable population.